Effect of Low-Energy-Dense Diet Rich in Multiple Functional Foods on Weight-Loss Maintenance, Inflammation, and Cardiovascular Risk Factors: A Randomized Controlled Trial. (4th July 2018) - Izadi, Vajihe; Haghighatdoost, Fahimeh; Moosavian, Parisa; Azadbakht, Leila
ABSTRACT: Background: There are no investigations regarding the effects of consuming low-energy-dense diets rich in multiple functional foods on weight-loss maintenance, inflammatory markers, and cardiovascular disease (CVD) risk factors simultaneously. Method: This randomized controlled trial design was conducted on 90 men and women who were under a previous weight loss diet. Three months of intervention with recruitment at Allzahra Hospital, Isfahan, Iran, was done. Intervention was conducted following achieving 7–11 kg weight loss. Participants were encouraged to consumed these three: an isocaloric control diet (50% of energy from carbohydrate, 35% from fat, 15% from protein), a low-glycemic-index diet (LE) (60% from carbohydrate, 25% from fat, and 15% from protein), and a low-glycemic-index diet rich in multiple functional foods (LE + FF) (60% from carbohydrate, 25% from fat, and 15% from protein). Fasting blood glucose, serum insulin level, lipid profiles, inflammatory markers, adiponectin, systolic and diastolic blood pressure, and anthropometric measurements were assessed using standard guidelines. Results: The percent changes of weight, waist, and body mass index (BMI), systolic and diastolic blood pressure, malondialdehyde (MDA), high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor (TNF) α, total cholesterol, low-density lipoprotein (LDL) cholesterol, triglyceride, and fasting blood glucose (FBS) were substantially more decreased in the LE + FF group compared to the LE and control groups ( p ≤ 0.03). Percent change of adiponectin among the LE + FF group was significantly more enhanced (7.29 ± 0.10) compared with the LE group (1.28 ± 0.20) ( p = 0.001). Significantly more increment in the percent change of total antioxidant capacity (TAC) (6.91 ± 0.10) was obtained among the LE + FF group compared to the LE group (1.79 ± 0.04). Conclusions: This study provides established evidence supporting the beneficial effects of a low-energy-dense diet rich in multiple functional foods diet on improving weight-loss maintenance, inflammation, and cardiovascular risk factors.